Dribble Deficit Enables Measurement of Dribbling Speed Independent of Sprinting Speed in Collegiate, Male, Basketball Players. Issue 7 (July 2021) - Ramirez-Campillo, Rodrigo; Gentil, Paulo; Moran, Jason; Dalbo, Vincent J.; Scanlan, Aaron T.
Abstract : Abstract: Ramirez-Campillo, R, Gentil, P, Moran, J, Dalbo, VJ, and Scanlan, AT. Dribble Deficit enables measurement of dribbling speed independent of sprinting speed in collegiate, male, basketball players. J Strength Cond Res 35(7): 2040–2045, 2021—The aim of this study was to determine the relationships between sprinting and dribbling speed in basketball during linear and change-of-direction (COD) sprints using total dribbling time and Dribble Deficit. Collegiate, male, basketball players ( n = 10; 21.0 ± 1.6 years) performed linear and COD sprints with and without dribbling a ball. Linear dribbling sprints were measured for the dominant and nondominant hands, whereas COD dribbling sprints involved bilateral use of hands. Dribble Deficit was determined as the difference between total time (second) during each dribbling trial and the equivalent nondribbling trial for linear and COD sprints. Simple linear regression analyses were performed during linear and COD sprints to determine the relationship ( R ) and shared variance ( R 2 ) between (a) sprinting times and total dribbling times and (b) sprinting times and Dribble Deficit. Large to very large, significant relationships were evident between linear sprinting and dribbling time for dominant ( R = 0.86; R 2 = 0.74, p = 0.001) and nondominant hands ( R = 0.80; R 2 = 0.65, p = 0.005). Trivial relationships were apparent between linear sprinting time and Dribble Deficit with dominant ( R = 0.10; R 2 = 0.01, p = 0.778) and nondominant hands ( R = 0.03; R 2 = 0.00, p = 0.940). A very large relationship was evident between COD sprinting and dribbling time ( R = 0.91; R 2 = 0.82, p < 0.001), whereas a trivial relationship was observed between COD sprinting time and COD Dribble Deficit ( R = −0.23; R 2 = 0.05, p = 0.530). Dribble Deficit eliminates the strong influence of sprinting speed on outcome measures typically seen when using tests predicated on total dribbling time. Consequently, Dribble Deficit may be of added use in basketball test batteries to measure dribbling speed across linear and multidirectional movement paths.